Review on Microemulsion for Nasal Drug Delivery - Bhonde G. Akash; Dr. Sandeep C. Atram; Mandwe S. Vrushabh; Bawankar V. Dipali; Puri G. Ashutosh (Asian Journal of Pharmaceutical Research and Development, 2025)
Bacterial meningitis remains a life-threatening central nervous system (CNS) infection with high morbidity and mortality rates, demanding rapid and effective therapeutic intervention. Traditional systemic antibiotic therapies often face challenges such as the blood-brain barrier (BBB) limiting drug penetration, systemic toxicity, and poor patient compliance. Nasal drug delivery emerges as a promising non-invasive alternative route to bypass the BBB and deliver therapeutic agents directly to the brain. Microemulsions, with their nanoscale droplet size, high solubilization capacity, and enhanced permeation properties, offer significant potential for intranasal delivery of antibiotics targeting CNS infections. This review focuses on the formulation strategies, key excipients, and evaluation parameters critical for developing effective microemulsion systems for nasal administration. It also discusses recent advances, in vitro and in vivo studies, pharmacokinetic aspects, and the challenges associated with the clinical translation of such systems. The integration of microemulsion technology with nasal drug delivery holds great promise for improving therapeutic outcomes in bacterial meningitis.